Short-term creep properties and fracture surface of 18 Ni (300) maraging steel plasma nitrided - Dos Reis, Adriano Gonçalves [UNESP]; Reis, Danieli Aparecida Pereira; Abdalla, Antônio Jorge; Couto, Antônio Augusto; Otubo, Jorge (FapUNIFESP (SciELO), 2017)
Plasma nitriding of a solution annealed and aged 300 grade maraging steel was studied aiming to increase the creep resistance. The surface microhardness reached 1,140 HV, producing 50 μm layer composed of ε-Fe3N and γ'-Fe4N nitrides at the uppermost sample layer. The inner core remained unaltered presenting typical plate-like martensite microstructure of maraging steels with average microhardness of 604 HV. Surface RMS roughness in the nanometric scale increase from 52 nm to 71 nm. The continuous layer of iron nitrides seems to behave as a barrier for oxidation and for inward oxygen diffusion improving the creep resistance by reducing the steady-state creep rate (εs) in 52-65% when compared with the literature results. Dominant creep mechanism is controlled by dislocations climb. Fracture surfaces of specimens presented ductile failure consisting of equiaxed and bi-modal dimples in the fibrous zone surrounded by 45ºshear lip. Nitrided sample presented a reduced ductility, associated to the hard surface layer.
Keywords: Creep; Fracture; Maraging; Plasma nitriding